2019
DOI: 10.1097/md.0000000000016696
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Guizhi Wuwu decoction for diabetic peripheral neuropathy

Abstract: Background: Diabetic peripheral neuropathy (DPN) is one of the most common causes of disability in diabetic population, and its pathogenesis is related to a variety of factors. There is currently no effective treatment for such chronic disease. Traditional Chinese medicine has a long clinical history for the prevention and treatment of diabetes and chronic complications, and it also shows certain advantages in the treatment of DPN. Many clinical studies have confirmed that Chinese medicine Huangqi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…This prescription has long been used to control pain and numbness in stroke sequelae, peripheral nerve injury, and other diseases. Recent studies and our work suggest that HGWD is therapeutically effective for diabetic and oxaliplatin-induced peripheral neuropathy [12,13]. HGWD improved neurological function, increased blood circulation and alleviated oxaliplatininduced mechanical and cold hypersensitivity, suggesting that HGWD may offer potential opportunities to CIPN treatment.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…This prescription has long been used to control pain and numbness in stroke sequelae, peripheral nerve injury, and other diseases. Recent studies and our work suggest that HGWD is therapeutically effective for diabetic and oxaliplatin-induced peripheral neuropathy [12,13]. HGWD improved neurological function, increased blood circulation and alleviated oxaliplatininduced mechanical and cold hypersensitivity, suggesting that HGWD may offer potential opportunities to CIPN treatment.…”
mentioning
confidence: 56%
“…Herbal formula HGWD has been used to treat numbness, vibration sensation, cold sensation, and limb ache since the Eastern Han Dynasty, which is considered a potential complementary therapy providing neuronal protection in chemotherapy [16]. Recently, HGWD has been proven to be effective in treating oxaliplatin-and diabetic peripheral neuropathy in animal models and clinical studies [12,13]. However, the effect of HGWD on PIPN with its pharmacological mechanism remains unclear, Thus, in this study, we tested whether HGWD alleviates PIPN and explore the underlying pharmacological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical evidence-based studies have shown that HGWWD has a positive therapeutic effect on various cardiovascular and cerebrovascular diseases. For example, HGWWD can improve cerebral blood flow in stroke patients and alleviate the subjective symptoms of diabetic peripheral neuropathy (Baiqing, 2015;Pang et al, 2016). Similarly, a recent study reported that HGWWD effectively treated lower extremity macroangiopathy in diabetic patients (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…[ 20 ] The mechanism of traditional Chinese medicine in treating DPN is protecting pancreatic cells, improving blood glucose and lipids, and delaying the disease's progression by antioxidant therapy. [ 21 , 22 ] Studies show that using three traditional Chinese medicine injections, including Danhong injection, Ginkgo leaf injection, and Danshen Chuanxiongqin injection, are better than using mecobalamin only in the adjuvant treatment of DPN. [ 23 ] The main components are tanshinone, Salviol, ginkgo biloba extract of Safflower, etc.…”
Section: Discussionmentioning
confidence: 99%